Kontekstualisasi Makna Penyelewengan Hak Istimewa dalam Hadis Kecelakan Umat di Tangan Para Pemuda Bodoh dari Quraysh - Hani Anggita Dewi; Syarifah Zifa Putri Andini; Farhan Abdillah; Dicky Alvian; Alfan Shidqon (Journal of Hadith Studies, 2025)
This article examines the reinterpretation of the ḥadīth concerning the destruction of the ummah at the hands of foolish youths from Quraysh (Halāk ummatī ‘alā yaday ughaylimah sufahā’ min Quraysh) in a sermon delivered by Gus Kautsar, a young preacher from the pesantren (Islamic boarding school) milieu. Utilizing a hermeneutical approach that includes linguistic analysis, micro-context (asbāb al-wurūd), and macro-context (the social structure of the Quraysh tribe during the Prophet’s ﷺ time), this study demonstrates that Gus Kautsar’s substitution of the phrase “youths of Quraysh” with “foolish gus” represents an effort to contextualize the ḥadīth’s meaning within contemporary social realities. In pesantren culture, gus—the sons of respected religious leaders—often inherit symbolic capital without the guarantee of scholarly or moral competence, much like the Quraysh elite in history. By emphasizing dynamic meaning, Gus Kautsar revives the ethical message of the ḥadīth as a form of internal social critique, showing that classical texts can remain relevant through contextual and ethical readings.